2021
DOI: 10.1002/aur.2512
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of medical morbidities in a rhesus monkey model of naturally occurring low sociality

Abstract: People with autism spectrum disorder (ASD) exhibit a variety of medical morbidities at significantly higher rates than the general population. Using an established monkey model of naturally occurring low sociality, we investigated whether lowsocial monkeys show an increased burden of medical morbidities compared to their high-social counterparts. We systematically reviewed the medical records of N = 152 (n = 73 low-social; n = 79 high-social) rhesus macaques (Macaca mulatta) to assess the number of traumatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 88 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…It is possible that, in an environment in which one's companions are relatively well-known, other mechanisms, such as avoidance, may mitigate the very real social deficiencies that have been demonstrated by low-social individuals (Capitanio, 1999(Capitanio, , 2002Capitanio et al, 2008). Nevertheless, in times of challenge, even in a familiar social environment, these social deficiencies may manifest themselves to an extent resulting in injury-as we have previously found (Myers et al, 2021). Clearly, more work is needed to understand the underlying psychological components of low sociality, and the contexts in which those components create social problems (and potential injuries) for the animals.…”
Section: Nonsocialmentioning
confidence: 74%
See 2 more Smart Citations
“…It is possible that, in an environment in which one's companions are relatively well-known, other mechanisms, such as avoidance, may mitigate the very real social deficiencies that have been demonstrated by low-social individuals (Capitanio, 1999(Capitanio, , 2002Capitanio et al, 2008). Nevertheless, in times of challenge, even in a familiar social environment, these social deficiencies may manifest themselves to an extent resulting in injury-as we have previously found (Myers et al, 2021). Clearly, more work is needed to understand the underlying psychological components of low sociality, and the contexts in which those components create social problems (and potential injuries) for the animals.…”
Section: Nonsocialmentioning
confidence: 74%
“…Possibly due to these inappropriate social responses, low-social monkeys also experience a higher rate of traumatic injury than highsocial monkeys (Myers et al, 2021). Thus, we hypothesized that lowsocial monkeys would initiate and receive a higher frequency of threat behavior compared to high-social monkeys.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, we acknowledge that subjects might have underlying personality traits that covary with or contribute to the risk of hospitalization. For instance, prior work has shown that adult subjects that were more frequently observed alone in a social group had higher trauma rates relative to more social individuals, independent of rank (Myers et al, 2021); similarly, subjects with lower ratings on the macaque Social Responsiveness Scale-Revised had higher rates of trauma, relative to high rated subjects (Myers et al, 2021). Elfenbein et al (2016) also demonstrated that higher scores on the BBA Nervous temperament factor were associated with increased occurrences of diarrhea, relative to individuals with lower ratings.…”
Section: Influence Of Experiencementioning
confidence: 99%
“…Accordingly, we have used naturally occurring low sociality in male rhesus monkeys to model and study the social interaction impairments of ASD [ 5 ], focusing on behavioral phenotyping, biomarker discovery, and pharmacological testing. This work has determined that low-social males initiate fewer social interactions [ 6 , 7 ], show abnormalities in species-typical perception of, and responses to, social stimuli [ 8 , 9 ], exhibit a greater burden of autistic-like traits [ 10 ], and incur more traumatic injuries [ 11 ] than their socially competent male peers. Naturally occurring low sociality is also stable within individual males across time [ 7 ], unrelated to dominance rank [ 7 , 9 , 10 , 12 ], and highly heritable [ 12 ].…”
Section: Introductionmentioning
confidence: 99%